PENGARUH BRAND POSITIONING DAN BIAYA WARALABA (FRANCHISE FEE) TERHADAP PEMBELIAN WARALABA (FRANCHISE PURCHASE) PADA USAHA MINUMAN “SEGARA” (Studi di Kota Semarang dan Kabupaten Kendal) - Rendy Ramanda; Yoestini Yoestini (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Competitive advantage in the franchise business can increase the interest of franchisees because it is considered to have a stable market, good reputation, and an established business. The franchisee's decision to purchase a franchise is based on what they value as providing benefits such as profit, and business continuity. This study aims to examine the effect of brand positioning and franchise fees on franchise purchases. This study uses a survey method and is distributed to the franchisee